Pengaruh Kreativitas Guru Dan Media Pembelajaran Terhadap Kinerja Mengajar Guru Pada SD Gugus Sei Miai Di Kecamatan Banjarmasin Utara - Sri Yenie; Rizalul Gadi; Mukhlan khariry; Singgih Priono; Riky Welli Saputra (Administraus, 2023)
This research aims to determine and analyze the influence of creativity and instructional media on the performance of elementary school teachers in the Sei Miai Cluster in North Banjarmasin District. The research method employed is descriptive quantitative research, with data sources consisting of primary and secondary data. Primary data is collected directly from the field through observation, surveys, and interviews, which include questions related to teacher creativity, instructional media, and teaching performance. Secondary data is gathered from various references and supporting data obtained during the research process. Data collection techniques in this study involve observation, questionnaires, and documentation, while data analysis utilizes multiple regression analysis. The research results indicate that in the partial t-test, the Sig values for the variables of creativity and instructional media are 0.003 and 0.002, respectively. The Sig values are smaller than the alpha coefficient (0.05), indicating that both creativity and instructional media have a significant influence on the performance of elementary school teachers in the Sei Miai Cluster in North Banjarmasin District. Furthermore, the simultaneous F-test shows that the Sig value for the independent variables is 0.000, which is also smaller than the alpha coefficient (0.05). This suggests that both creativity and instructional media together have a significant impact on the performance of elementary school teachers in the Sei Miai Cluster in North Banjarmasin District. Keywords: Teacher creativity; Instructional media; Teacher performance; Influence of creativity; Influence of instructional media